Hak Milik Di Atas Tanah Hak Ulayat Negeri Halong - Sachmad, Yuniar; Saija, Ronald; Fataruba, Sabri (Pusat Kajian Pesisir dan Masyarakat Hukum Adat Fakultas Hukum Universitas Pattimura, 2023)
This research discusses the Juridical Analysis of Property on Negen Halong Customary Land (Case Study of Supreme Court Cassation Decision Number 2879 K/Pdt/2019) which is the disputed land. This study aims to further discuss the juridical ownership rights over the customary land of Negen Halong. This research uses the juridical normative method by using a statutory approach, a conceptual approach, and a case approach. The results of the research show that the Supreme Court Judge’s Consideration in the Cassation Decision Number 2879 K/Pdt/2019) considers that against these reasons the Supreme Court is of the opinion that the reasons for cassation cannot be justified, due to legal consideration and the decision of the judex facti/Ambon High Court which annulled the decision of the Ambon District Court was correct and correct and not wrong in applying the law. Dictum of the Supreme Court Decision in Decision Number 2879 K/Pdt/2019 that after this final decision was notified to the applicant for cassation on 15 February 2019, then the petition for cassation was filed against him on 27 February 2019, as it turns out from the Deed of Request for cassation Number 6K/Pdt.G/2019/PN.Amb made by the Registrar of the Ambon District Court, the application was followed by a cassation memory containing the reasons received at the Registrar’s office of the District Court on March 6 2019.